The perceived quality, value and satisfaction of a sports club. The prospect of parents and adult athletes - Matías Camino López; Jerónimo García Fernández (Federación Extremeña de Balonmano; University of Extremadura, 2014)
Due to the interest in knowing the perception of sports services, this study has the objective to assess the perceived quality, value and satisfaction of sports club basketball parents and adult athletes, and to examine the relationship between these variables. Sample was composed by 112 users (33 women and 79 men) of a basketball sport club, being realized first an analysis descriptive, second an exploratory factorial analysis, an analysis of variance and finally linear regressions. Results show a reliable and valid instrument composed by five dimensions (activity, facilities, material, staff and communication) where the activity and staff dimensions were the best rated. At last before linear regressions' study, a significant relationship was found between perceived quality and perceived value, especially in activity and personal dimensions. Also a relationship between perceived value and satisfaction was established.